Passive discomfort index as an alternative to predicted mean vote and predicted percentage of dissatisfied to assess occupant’s thermal discomfort in dwellings - Soares dos Reis, Alexandre (2022)
Besides energy poverty, a certain tolerance to discomfort justifies Portugal's low heating energy consumption. Once Portuguese buildings stock, previous to 1990, has a weak energy performance, it is crucial to reflect on how to make renovations with more assertive benefits (besides energy), such as those related to the health and comfort of occupants. Hence, we have studied a single house in the TRNSYS dynamic simulation tool. We performed a sensitivity analysis by simulating the same building in three locations based on Portuguese climatic winter zones: I1 – Santarém, I2 – Santa Maria da Feira, and I3 – Guarda, for two ranges of wall insulation thickness, in free float. Considering Fanger's Predicted Mean Vote (PMV) and Predicted Percentage of Dissatisfied (PPD) as the Passive Discomfort Index IDP, results suggest that lowering 20 mm on the insulation thickness does not substantially impact occupants' discomfort in winter. As the variations between scenarios considering PPD > 15%, PMV < -1, or IDP (Tair < 18 ºC) are very similar, IDP could be an alternative to PMV/PPD for assessing thermal discomfort in dwellings.